2005
DOI: 10.1093/ejo/cji067
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue facial profile changes following functional appliance therapy

Abstract: The aim of this study was to evaluate changes in the facial profile resulting from the use of a twin block (TB) functional appliance. The sample comprised 38 patients (24 males and 14 females) with a Class II division 1 malocclusion. Nineteen subjects were treated with a functional appliance while the remaining 19, who did not undergo any intervention, served as the control. The mean age of the treated group was 9.5 years (SD 10 months) and of the control group 9.9 years (SD 13 months). Lateral cephalograms we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 27 publications
5
68
0
7
Order By: Relevance
“…It was found that a sample of 11 individuals was need to detect a difference of at least 1400 mm 3 with standard deviation of 1650 mm 3 as found by our preliminary studies (unpublished data). Multivariate ANOVA was used to evaluate the effect of functional appliances on the experimental variables when controlling for CVMS as previously described.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…It was found that a sample of 11 individuals was need to detect a difference of at least 1400 mm 3 with standard deviation of 1650 mm 3 as found by our preliminary studies (unpublished data). Multivariate ANOVA was used to evaluate the effect of functional appliances on the experimental variables when controlling for CVMS as previously described.…”
Section: Discussionsupporting
confidence: 54%
“…The inferior limit was that spanning the A-P dimension of the airway, passing through the tip of the epiglottis (Figure 2). The airway sensitivity setting, which controls the program's ability to find differences in gray-scale resolution, was standardized at 45 to best recognize the airway and calculate the volume in mm 3 .…”
Section: Oropharyngeal Airway Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The skeletal and dentoalveolar effects of functional appliances are almost always accepted by researchers; [13][14][15] however, with regard to aesthetic improvement, evaluation of soft tissue profile alterations after treatment with functional appliances is of great importance. The ultimate test for treatment lies in its ability to bring about visible changes and its long-term stability in terms of aesthetics and function.…”
Section: Introductionmentioning
confidence: 99%
“…O desenvolvimento normal dos lábios durante os anos acompanha o crescimento dos músculos e de outros tecidos conectivos com o corpo (QUINTAO et al, 2006;TALASS;TALASS;BAKER, 1987).…”
Section: Introductionunclassified